Extreme work/normal work: Intensification, storytelling and hypermediation in the (re)construction of 'the New Normal'. (July 2015) - Granter, Edward; McCann, Leo; Boyle, Maree
The label 'extreme' has traditionally been used to describe out-of-the-ordinary and quasi-deviant leisure subcultures which aim at an escape from commercialized and over-rationalized modernity or for occupations involving high risk, exposure to 'dirty work' and a threat to life (such as military, healthcare or policing). In recent years, however, the notion of 'extreme' is starting to define more 'normal' and mainstream realms of work and organization. Even in occupations not known for intense, dirty or risky work tasks, there is a growing sense in which 'normal' workplaces are becoming 'extreme', especially in relation to work intensity, long-hours cultures and the normalizing of extreme work behaviours and cultures. This article explores extreme work via a broader discussion of related notions of 'edgework' and 'extreme jobs' and suggests two main reasons why extremity is moving into everyday organizational domains; the first relates to the acceleration and intensification of work conditions and the second to the hypermediation of, and increased appetite for, extreme storytelling. Definitions of extreme and normal remain socially constructed and widely contested, but as social and organizational realities take on ever more extreme features, we argue that theoretical and scholarly engagement with the extreme is both relevant and timely.